Curiosity in Science Learning: A Systematic Literature Review - Hunaepi, H.; Suma, I Ketut; Subagia, I Wayan (International Journal of Essential Competencies in Education, 2024)
This review systematically examines the role of curiosity in science learning, focusing on its influence on engagement, cognitive processes, and educational outcomes. A comprehensive literature search was conducted using databases such as Scopus, resulting in the selection of 40 peer-reviewed empirical studies published between 2019 and 2024. Inclusion and exclusion criteria ensured the relevance and rigor of the selected studies. The findings reveal that curiosity significantly enhances memory encoding and consolidation, motivates learners, and supports exploratory behavior. Specifically, studies indicated that curiosity-driven learning leads to improved attention and learning processes, resulting in better educational outcomes. Pedagogical strategies that foster curiosity, including the integration of large language models and innovative teaching tools, have been shown to effectively enhance student engagement and learning in science. Quantitative data from the reviewed studies demonstrate that curiosity-driven approaches lead to a 25% increase in student engagement and a 30% improvement in learning outcomes. The review underscores the importance of systematically integrating curiosity-enhancing strategies within pedagogy to create more engaging and effective educational experiences. Future research should focus on developing comprehensive measurement tools for assessing curiosity and conducting longitudinal studies to explore its long-term impact on academic achievement and skill development. Additionally, the exploration of modern technologies in enhancing curiosity-driven learning should be prioritized. Educators are encouraged to implement pedagogical strategies that stimulate curiosity to maintain and enhance student engagement and achievement in science learning.